1995
DOI: 10.1152/ajpcell.1995.268.6.c1395
|View full text |Cite
|
Sign up to set email alerts
|

Rat muscle branched-chain ketoacid dehydrogenase activity and mRNAs increase with extracellular acidemia

Abstract: The rate-limiting enzyme in branched-chain amino acid catabolism is branched-chain ketoacid dehydrogenase (BCKAD). In rats fed NH4Cl to induce acidemia, we find increased basal BCKAD activity as well as maximal activity in skeletal muscle. Concurrently, there is a > 10-fold increase in mRNAs of BCKAD subunits in skeletal muscle plus an increase in cardiac muscle but not in liver or kidney. There was no increase in mRNA for malate dehydrogenase or for cytosolic glyceraldehyde-3-phosphate dehydrogenase. Evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 18 publications
3
30
1
Order By: Relevance
“…In our study, leucine oxidation rates across the kidney tended to be lower in acidemic subjects, indicating that amino acid oxidation is not increased by metabolic acidosis in the kidney, in agreement with studies showing no change in branched-chain ketoacid dehydrogenase activity in the kidneys of acidotic rats (30,31).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, leucine oxidation rates across the kidney tended to be lower in acidemic subjects, indicating that amino acid oxidation is not increased by metabolic acidosis in the kidney, in agreement with studies showing no change in branched-chain ketoacid dehydrogenase activity in the kidneys of acidotic rats (30,31).…”
Section: Discussionsupporting
confidence: 92%
“…Metabolic acidosis causes accelerated proteolysis by enhancing the activity of ATP-dependent ubiquitin-proteasome system (28) and the enzyme branch-chain ketoacid dehydrogenase (29). However, we found that bicarbonate supplement improved SGA score for anorexia and NPNA.…”
Section: Discussioncontrasting
confidence: 58%
“…The ingestion of 0.28 M of NH 4 Cl for 10 days markedly decreased aortic blood-pH values and serum-bicarbonate concentrations ( Table 1), indicating that a metabolic acidosis was caused by this treatment, like previous results in other experimental chronic acidosis experiments (2,15). No significant differences were detected in weight and intake between the two experimental groups.…”
Section: Resultssupporting
confidence: 79%